Progressive Pseudo-Analog Transmission for Mobile Video Streaming - He, Dongliang; Lan, Cuiling; Luo, Chong; Chen, Enhong; Wu, Feng; Zeng, Wenjun (IEEE Transactions on Multimedia, 2017)
We propose a progressive pseudo-analog video transmission scheme which simultaneously handles SNR and bandwidth variations with graceful quality degradation for mobile video streaming. With the inherited SNR-adaptability from pseudo-analog transmission, the proposed progressive solution acquires bandwidth-adaptability through an innovative scheduling algorithm with optimal power allocation. The basic idea is to aggressively transmit or re-transmit important coefficients so that distortion is minimized at the receiver after each received packet. We derive the closed-form expression of reduced distortion for each packet under given transmission power and known channel conditions, and show that the optimal solution can be obtained with a water-filling algorithm. We also illustrate through analyses and simulations that a near-optimal solution can be found through approximation when only statistical channel information is available. Simulations show that our solution approaches the performance upper bound of pseudo-analog transmission in an AWGN channel and significantly outperforms existing pseudoanalog solutions in a fast Rayleigh fading channel. Trace-driven emulations are also carried out to demonstrate the advantage of the proposed solution over the state-of-the-art digital and pseudoanalog solutions under a real dramatically varying wireless environment. Progressive Pseudo-Analog Transmission for Mobile Video Streaming. Available from: https://www.researchgate.net/publication/315587257_Progressive_Pseudo-Analog_Transmission_for_Mobile_Video_Streaming [accessed Jan 03 2018].